Perbedaan Penurunan Tekanan Darah Antara Pemberian Propofol Dan Propofol Kombinasi Fentanyl Pada Induksi Anestesi - Andang Andang; Nabhani Nabhani; Fadhilla Nur Rahmansyah (Journal Pharma Saintika, 2020)
Background of the Research: General anesthesia have a risk to cause side effects of hemodynamic response disorder. Hemodynamic stability in the use of propofol as an induction drug can be considered by administering fentanyl prior to induction of propofol anesthesia. Aim of the Research: to know the difference of decreasing blood pressure with recofol induction and combination of fentanyl recofol. Research Method: The design of this research is observational eksperimental with 30 samples of patients undergoing surgery who meet the inclusion and exclusion criteria at IBS Rs Bhayangkara Brimob for April 2022. It is divided into two groups: First group uses Propofol 2 mg/kg intravenous BB, second group uses fentanyl 1 mcg/kg intravenous BB and 2 mg/kg intravenous BB. Systolic blood pressure and diastolic blood pressure, mean arterial pressure were recorded at minute 1.3 and 5 after induction. The data analysis uses SPSS 22 For Window program. The results showed that there was a difference in the decrease in TDS with a p value of 0.000 <0.05. In TDD there was a significant difference with a sig value of 0.005 <0.05 which was significant in the administration of Propofol and the combination of Fentanyl-Propofol, but there was no significant difference in TAR in the two groups with a sig value of 0.371> 0.05. Conclusion: there is a difference in the incidence of lowering blood pressure between recofol induction and the combination of Fentanyl-Propofol.